Historically Black Colleges and Universities
IX, 252 p.
Keywords: Historically Black colleges and universities play a vital role in the education of African Americans in the United States. For nearly 150 years, these institutions have trained the leadership of the Black community, graduating the nation s African American teachers, doctors, lawyers, and scientists. Despite the wealth of new research on Black colleges, there are topics that remain untouched and accomplishments that go unnoticed by the scholarly community. The chapters in this edited volume focus on topics that deserve further attention and that will push students, scholars, policymakers, and Black college administrators to reexamine their perspectives on and perceptions of Black colleges.